Anisotropic ESCRT-III architecture governs helical membrane tube formation - Joachim Moser von Filseck (Nature Portfolio, 2020)
ESCRT-III proteins assemble into ubiquitous membrane-remodeling polymers during many cellular processes. Here, the authors use cryo-ET, cryo-EM and mathematical modeling to reveal how the shape of the helical membrane tube arises from the assembly of two distinct bundles of helical filaments.